Towards a definition of refractory/therapy-resistant/intractable constipation in children: a cross-sectional, questionnaire-based, online survey - Marc A Benninga; Morris Gordon; Shaman Rajindrajith; Vassiliki Sinopoulou; Merit Tabbers; Carlos Velasco; Wathsala Hathagoda; Mansour Abdulshafea (BMJ Paediatrics Open)
Background The Rome criteria define childhood functional constipation but do not address refractory constipation. Attempts to define refractory constipation lack consensus. The interchangeable use of ‘refractory’ and ‘intractable’ or ‘therapy-resistant’ constipation and lack of understanding of the therapeutic ceilings before this diagnosis complicates the definition.Aim To conduct an online cross-sectional study among medical professionals and researchers across a range of countries, to propose a consensus definition, terminology and duration of medically unresponsive constipation.Method An expert-designed questionnaire was disseminated via Google Forms in a two-stage study over 2 months targeting paediatric gastroenterology professionals globally and Latin American clinicians with a translated version. The questionnaire had seven critical questions containing details needed to define medically unresponsive constipation. The study protocol was approved by the ethics review panel.Results The survey involved 1079 participants: 87 from various countries in the first phase and 992 from Latin America in the second. There were 619 (57.3%) general paediatricians and 462 (43 %) paediatric gastroenterologists. The preferred term to indicate poorly responding constipation was ‘therapy-resistant constipation’ (47.8%), followed by ‘refractory constipation’ (43.6%). The majority of respondents (92.9%) agreed on considering a time frame for defining refractory constipation, with 37.7% suggesting 2–3 months. 467 (43.2%) recommended including failure despite maximum laxative therapy with two agents should be considered as previous therapy failure. Compliance with therapy was deemed essential for successful treatment by 91.1%, assessed through detailed history-taking (47.4%) or medical/pharmacy records (29.4%).Conclusion Based on the professional views collected in this study, we propose the term ‘therapy-resistant constipation’ and it can be defined as constipation that is not responding to a maximum dose of at least two laxatives of different classes for a minimum of 3 months with good compliance in a secondary or tertiary care facility.